Work-related road safety: An analysis based on U.K. bus driver performance - Dorn, Lisa; af Wåhlberg, Anders E. (Blackwell Publishing Ltd, 2008)
The effects of age and experience on accident involvement for bus drivers were investigated, with special emphasis upon the first years of being an operator, using two methods. First, direct calculations between these variables were undertaken. Thereafter, a variant of the method of quasi-induced exposure (a ratio of culpable versus nonculpable accidents in the population) was used and referred to as the indirect method. These methods yielded fairly similar results, given that the samples used were drawn from the same population but only partly overlapping. It was found that experience had the strongest effect on accidents in the first year of driving, while age had a u-shaped association with accidents, that is, young and old drivers had more accidents, something that was more apparent when experience was held constant. These results show that, for bus drivers, experience is initially more important than age, but after two or three years, the effect is small. Thereafter, age is the more discernible variable, although it is a very weak factor in predicting crash risk.
Keywords: accident bus driver crash, culpability, quasi-induced exposure quasi-induced exposure accident involvement driving performance personality-factors crash involvement age experience identification variables mistakes